Teaching and Teacher Education in International Contexts : ISATT 40th Anniversary Yearbook - Craig, Cheryl J.; Mena, Juanjo; Kane, Ruth, 1957- (Advances in research on teaching, 2023)
The ISATT 40thAnniversary Yearbook, presented over three volumes, celebrates the contributions of ISATT members over time and offers current scholarly research to inform current and future teacher education and teaching.